Answer:
The answer is C.
Step-by-step explanation:
The simplest form is C.
Answer:
(1, 3), (2, 6), (3, 9)
Step-by-step explanation:
Dividing the first given ratio by 7 gives ...
7/7 : 21/7 = 1 : 3
Multiplying this by 2 and 3 gives the other ratios you want.
= 2(1) : 2(3) = 2 : 6
= 3(1) : 3(3) = 3 : 9
The equivalent ratios are (1, 3), (2, 6), (3, 9).
x=3 and x= -2
Step-by-step explanation:
we could simplify it to x*2 + x -6 = 0
then 2 numbers whose sum is 1 and product is -6
the numbers are 3 and -2
hmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmm
Answer:
C 1,844
Step-by-step explanation: